Neoarchean granite-greenstone belts and related ore mineralization in the North China Craton: An overview - Li Tang (Geoscience Frontiers, 2018)
Tectonic processes involving amalgamations of microblocks along zones of ocean closure represented by granite-greenstone belts (GGB) were fundamental in building the Earth's early continents. The crustal growth and cratonization of the North China Craton (NCC) are correlated to the amalgamation of microblocks welded by 2.75–2.6 Ga and ∼2.5 Ga GGBs. The lithological assemblages in the GGBs are broadly represented by volcano-sedimentary sequences, subduction-collision related granitoids and bimodal volcanic rocks (basalt and dacite) interlayered with minor komatiites and calc-alkalic volcanic rocks (basalt, andesite and felsic rock). The geochemical features of meta-basalts in the major GGBs of the NCC display affinity with N-MORB, E-MORB, OIB and calc-alkaline basalt, suggesting that the microblocks were separated by oceanic realm. The granitoid rocks display arc signature with enrichment of LILE (K, Rb, Sr, Ba) and LREE, and depletion of HFSE (Nb, Ta, Th, U, Ti) and HREE, and fall in the VAG field. The major mineralization includes Neoarchean BIF-type iron and VMS-type Cu-Zb deposits and these, together with the associated supracrustal rocks possibly formed in back-arc basins or arc-related oceanic slab subduction setting with or without input from mantle plumes. The 2.75–2.60 Ga TTG rocks, komatiites, meta-basalts and metasedimentary rocks in the Yanlingguan GGB are correlated to the upwelling mantle plume with eruption close to the continental margin within an ocean basin. The volcano-sedimentary rocks and granitoid rocks in the late Neoarchean GGBs display formation ages of 2.60–2.48 Ga, followed by metamorphism at 2.52–2.47 Ga, corresponding to a typical modern-style subduction-collision system operating at the dawn of Proterozoic. The late Neoarchean komatiite (Dongwufenzi GGB), sanukitoid (Dongwufenzi GGB and Western Shandong GGB), BIF (Zunhua GGB) and VMS deposit (Hongtoushan-Qingyuan-Helong GGB) have closer connection to a combined process of oceanic slab subduction and mantle plume. The Neoarchean cratonization of the NCC appears to have involved two stages of tectonic process along the 2.75–2.6 Ga GGB and ∼2.5 Ga GGBs, the former involve plume–arc interaction process, and the latter involving oceanic lithospheric subduction, with or without arc-plume interaction. Keywords: North China Craton, Granite greenstone belt, Neoarchean, Plate and plume tectonics, Metallogeny